ESG Disclosure, Board Diversity, and Company Performance - Tifani, Savira Sarah; Naimah, Zahroh (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines the impact of ESG disclosure and board gender diversity on the performance of non-financial firms listed on the Indonesia Stock Exchange from 2018 to 2023. Grounded in Legitimacy, Agency, and Stakeholder theories, it employs multiple linear regression on 394 firm-year observations. Results show that ESG disclosure and gender diversity significantly enhance firm performance (ROE). However, their interaction shows a weaker effect, indicating limited synergy. The findings underscore the importance of advancing ESG transparency and gender-balanced leadership to support sustainable growth and long-term corporate performance.